Do Ghana’s Financial Sector Reforms Improve Competition of Banks?: An analysis with the Application of Panzar and Rosse Model - George Owusu-Antwi; James Antwi (Contemporary Research in Business, Management and Economics Vol. 4, 2024)
Since the early 1980s, there has been a major financial liberalization and institutional reforms program, a severe and protracted economic crisis, and the pre-reform policies of the government of Ghana over financial markets had damaged the financial system, resulting to financial volatility and bank distress. In the early 1990s, the government launched a financial market liberalization policy under the Financial Sector Adjustment Program (FINSAP), supported by the International Monetary Fund and the World Bank to restructure the distressed banks and clean up nonperforming assets to restore the banks to profitability and viability. The study investigated the market structure of Ghana’s banking industry and determined whether the market structure has changed after the financial restructuring. This study specifically measures the degree of competition in the banking system in Ghana by using the H-statistics. Various studies on the degree of competition were reviewed. This study employs a widely used nonstructural methodology put forward by Panzar and Ross [1]—the H-statistic—and draws upon comprehensive average annual data from the various issues of the Bank of Ghana annual reports from 1988 to 2011. Based on the reported H-statistic, it can be concluded that Ghana’s banks are operating under perfect conditions. However, the test for a change in competition status at the time of liberalization was not significant, indicating no evidence of a change in competition as a result of liberalization. This study has extended and strengthened some earlier results on bank competition in Ghana. However, the results of this study are different from the study undertaken by Buchs and Mathisen [2], who found Ghanaian banking markets to operate under monopolistic conditions. The conclusion of this study shows a variety of specifications controlling for bank size, risk, and various deposit composition characteristics, and several estimation techniques.